Unraveling the kinetics of the structural development during polymerization-induced self-assembly: decoupling the polymerization and the micelle structure. Issue 8 (17th January 2020) - Takahashi, Rintaro; Miwa, Shotaro; Sobotta, Fabian H.; Lee, Ji Ha; Fujii, Shota; Ohta, Noboru; Brendel, Johannes C.; Sakurai, Kazuo
Abstract : Upon extending a hydrophobic polymer chain from the end of a preceding hydrophilic chain in aqueous solutions, the resultant block copolymers may eventually undergo self-assembly. Abstract : Upon extending a hydrophobic polymer chain from the end of a preceding hydrophilic chain in aqueous solutions, the resultant block copolymers may eventually undergo self-assembly. Further chain propagation continues in the newly formed hydrophobic polymer rich domain. This process is often referred to as polymerization-induced self-assembly (PISA). Its kinetics are determined by the polymerization and the micelle formation/growth, which may influence each other, possibly leading to a highly complex process of structural development. In this study, we examined PISA in aqueous solution on the reversible addition fragmentation chain transfer (RAFT) dispersion polymerization of poly( N -acryloylmorpholine)- b -poly( N -acryloylthiomorpholine). Using in situ small-angle X-ray scattering (SAXS) and nuclear magnetic resonance spectroscopy (NMR), the polymerization and micelle formation were observed. In the analysis, because the time scale of the micelle formation/growth is much shorter than that of the polymerization, the polymerization and micelle fomarion/growth can be decoupled. Thus, these were separately analyzed in depth, and a combination of the kinetics of RAFT polymerization and the simple scaling theory of the micellar structures can quantitatively describe the overall micellar structural development during PISA. This study provides an unprecedented insight into the processes underlying PISA and deepens our quantitative understanding of it.